Risk factors for generalized anxiety disorder among young women and men in informal settlements in South Africa: A cross-sectional study - Smanga Mkhwanazi; Andrew Gibbs (Elsevier, 2021)
Generalized anxiety disorder (GAD) is common globally, particularly among young people, but limited research has been done on the risk factors for GAD especially in low-income settings. We sought to understand risk factors for GAD among young (ages 18-32) women and men from urban informal settlements in Durban, South Africa, enrolled in an intervention trial. Descriptive statistics and multivariable logistic regressions were used to assess risk factors, separately by sex. Using the GAD7 scale, among 484 women, 18.6 ​% reported moderate or severe symptoms of GAD. In multivariable analysis, moderate or severe GAD symptoms were associated with stealing because of hunger in the past month, stress because of lack of work, experiencing three or more past year experiences of adverse events, and past year experience of intimate partner violence. Among 505 men, 19.6 ​% reported moderate or severe GAD symptoms. In multivariable analysis, moderate or severe GAD symptoms were associated with stealing because of hunger in the past month, greater adverse childhood experiences, and three or more adverse experiences in the past year. Overall higher GAD symptoms were associated with poverty and violence experience and exposure, addressing these two factors is critical for reducing poor mental health.